2012
DOI: 10.3390/ijms13056220
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative Characteristics of Anisomeles indica Extract and Inhibitory Effect of Ovatodiolide on Melanogenesis

Abstract: The purpose of the study was to investigate the antioxidant characteristics of Anisomeles indica methanol extract and the inhibitory effect of ovatodiolide on melanogenesis. In the study, the antioxidant capacities of A. indica methanol extract such as DPPH assay, ABTS radical scavenging assay, reducing capacity and metal ion chelating capacity as well as total phenolic content of the extract were investigated. In addition, the inhibitory effects of ovatodiolide on mushroom tyrosinase, B16F10 intracellular tyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 35 publications
(37 reference statements)
0
17
0
Order By: Relevance
“…The results of this study show that essential oil extracted from the leaves of A. macrospadiceus significantly inhibits mushroom tyrosinase; thus, the essential oil may act as a possible tyrosinase inhibitor. It has been found that kojic acid is not effective in inhibiting melanin production or cellular tyrosinase in B16F10 cells [12, 13]. Thus, arbutin was selected as a positive standard in the following evaluation of intracellular melanin content and tyrosinase activity in B16F10 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study show that essential oil extracted from the leaves of A. macrospadiceus significantly inhibits mushroom tyrosinase; thus, the essential oil may act as a possible tyrosinase inhibitor. It has been found that kojic acid is not effective in inhibiting melanin production or cellular tyrosinase in B16F10 cells [12, 13]. Thus, arbutin was selected as a positive standard in the following evaluation of intracellular melanin content and tyrosinase activity in B16F10 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The reducing power of the A. macrospadiceus essential oil was determined according to a method described in previous work [13]. Different concentrations of A. macrospadiceus essential oil (0.012, 0.06, 0.12 mg/mL), vitamin C (0.105 mg/mL), or BHA (0.1 mg/mL) were mixed with phosphate buffer (2.5 mL, 0.2 M, pH 6.6) and potassium ferricyanide (K 3 Fe(CN) 6 ) (2.5 mL, 1% w/v).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the aqueous extract of A. indica has been shown to possess anti-histaminergic, anti-hyperalgesic and analgesic activities [26,27]. In addition, ethanol extract of A. indica exhibits anti-bacterial activity [28], and methanol extract displays antioxidant capacities [10]. Moreover, the constituents of A. indica have potent in vitro inhibitory effects on the production of the inflammatory mediators nitric oxide, tumor necrosis factor (TNF-α), and interleukin-12 (IL-12) [25].…”
Section: Discussionmentioning
confidence: 99%
“…Anisomeles indica Kuntze, which is commonly known as "yu-zhen-tsao", is the only species of Anisomeles found in Taiwan [8,9]. It is used in folk medicine for the treatment of diverse conditions, such as inflammatory disease, liver disease, intestinal infections, abdominal pain and immune system deficiencies [10]. Although A. indica has been used for health improvement in Taiwan, its anti-fatigue effects have not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Anisomeles ovata R. Br, also known as Anisomeles indica Kuntz., is the only species of the Labiatae family found in Taiwan and has been widely used as a herbal remedy to treat inflammation-related liver and skin diseases, hypertension and immune deficiencies [6]. Recent studies have suggested that Anisomeles ovata extracts exert various biological activities, including anti-oxidant, anti-inflammatory and tumor cell proliferation inhibitory [7][8][9][10], however, the underlying pharmacological mechanisms are still unclear. In order to identify the active ingredients of Anisomeles ovata, a number of chemical components have been identified, including flavonoids, terpenoids and steroids [9,[11][12][13].…”
Section: -Tdmf Possesses Weak or No Cytotoxicity Toward The Experimementioning
confidence: 99%